2018
DOI: 10.3389/fmicb.2018.02541
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Antibiofilm Activity of Synergistic Combinations of a Commercially Available Small Compound Library With Colistin Against Pseudomonas aeruginosa

Abstract: Biofilm-associated Pseudomonas aeruginosa infections remain a significant clinical challenge since the conventional antibiotic treatment or combination therapies are largely ineffective; and new approaches are needed. To circumvent the major challenges associated with discovery of new antimicrobials, we have screened a library of compounds that are commercially available and approved by the FDA (Prestwick Chemical Library) against P. aeruginosa for effective antimicrobial and anti-biofilm activity. A prelimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 46 publications
1
36
1
1
Order By: Relevance
“…However, the discovery of the mcr-1-carrying plasmid in 2015 broke the last barrier between superbugs and humans, and new therapies or drugs are urgently needed. Although several nonantibiotics that are synergistic with polymyxins were reported recently, most of them were evaluated in vitro (10,(16)(17)(18), and only a few compounds have been evaluated in animal models (11,(19)(20)(21). Hence, we screened a clinical compound library to search for new compounds that can potentiate colistin efficacy and discovered that one class of chemicals, PFK-158 and its analogs, could fight against polymyxin-resistant pathogens when used together with colistin.…”
Section: Discussionmentioning
confidence: 99%
“…However, the discovery of the mcr-1-carrying plasmid in 2015 broke the last barrier between superbugs and humans, and new therapies or drugs are urgently needed. Although several nonantibiotics that are synergistic with polymyxins were reported recently, most of them were evaluated in vitro (10,(16)(17)(18), and only a few compounds have been evaluated in animal models (11,(19)(20)(21). Hence, we screened a clinical compound library to search for new compounds that can potentiate colistin efficacy and discovered that one class of chemicals, PFK-158 and its analogs, could fight against polymyxin-resistant pathogens when used together with colistin.…”
Section: Discussionmentioning
confidence: 99%
“…23,50 Similar to our findings, multiple membrane-active compounds with synergistic interaction with colistin have been identified (Table 6) in previous studies. 13,15,19,24,25,27 A urea-containing class of 2-aminoimidazole-based adjuvants potentiated colistin activity against Col S A. baumannii with a reduction of colistin MIC by 1000fold, and increased survival (36-50%) of G. mellonella larva by exhibiting a membrane-permeabilizing effect in the bacteria. 13 Eugenol, an essential oil derived from clove, also potentiated the activity of colistin (MIC reduction up to 8-fold) against multiple Col R E. coli isolated from different animals (duck, goose, avian, porcine, zebra, fox, and peacock) by affecting the bacterial membrane integrity.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we investigated the adjuvant potential of previously identified membrane-acting small molecules (SMs) 23 with colistin against APEC. Because of the membrane-affecting properties of these SMs, 23 similar to previously identified colistin adjuvants which have been shown to potentiate the colistin effect by disrupting as well as permeabilizing the bacterial membrane, 19,21,24,27 these SMs can work synergistically with colistin, which is also a membrane-active antibiotic; 2 thereby, augmenting the colistin mediated disruption of the bacterial membrane.…”
Section: Introductionmentioning
confidence: 87%
“…While this hypothesis-guided approach is potentially promising, it is limited by our poor understanding of the complexity of on November 1, 2020 by guest http://aem.asm.org/ Downloaded from regulation that underlies transition to the biofilm state. As an alternative strategy, several recent studies relied on systematic large-scale screening of drugs for their biocidal activity against planktonic cell cultures, with a subsequent retesting of identified biocidal compounds for their antibiofilm activity (28,29). This approach enables identification of the biocidal compounds that are similarly active against planktonic and biofilm cultures, but it is unlikely to yield antibiofilm compounds that do not suppress planktonic growth.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we screened the Prestwick Chemical Library of over 1000 of FDAapproved drugs with the aim to identify new compounds that are active against on November 1, 2020 by guest http://aem.asm.org/ Downloaded from submerged biofilms of E. coli. This library has been recently used to identify drugs that impact human gut bacteria (26) or inhibit growth of several pathogenic bacteria in planktonic culture and also in biofilms (27)(28)(29). In contrast, the prime focus of our screen was to identify drugs that specifically inhibit E. coli biofilm formation, while having less or no effect on the planktonic growth.…”
Section: Introductionmentioning
confidence: 99%